A case‐control analysis of stroke in COVID‐19 patients: Results of unusual manifestations of COVID‐19–study 11. (29th September 2021) - García‐Lamberechts, Eric Jorge; Miró, Òscar; Fragiel, Marcos; Llorens, Pere; Jiménez, Sònia; Piñera, Pascual; Burillo‐Putze, Guillermo; Martín, Alfonso; Martín‐Sánchez, Francisco Javier; Jacob, Javier; Alquézar‐Arbé, Aitor; Ejarque Martínez, Laura; et al.
Abstract: Objective: We investigated the incidence, predictor variables, clinical characteristics, and stroke outcomes in patients with COVID‐19 seen in emergency departments (EDs) before hospitalization. Methods: We retrospectively reviewed all COVID‐19 patients diagnosed with stroke during the COVID‐19 outbreak in 62 Spanish EDs. We formed two control groups: COVID‐19 patients without stroke (control A) and non–COVID‐19 patients with stroke (control B). We compared disease characteristics and four outcomes between cases and controls. Results: We identified 147 strokes in 74, 814 patients with COVID‐19 seen in EDs (1.96‰, 95% confidence interval [CI] = 1.66‰ to 2.31‰), being lower than in non–COVID‐19 patients (6, 541/1, 388, 879, 4.71‰, 95% CI = 4.60‰ to 4.83‰; odds ratio [OR] = 0.42, 95% CI = 0.35 to 0.49). The estimated that standardized incidences of stroke per 100, 000 individuals per year were 124 and 133 for COVID‐19 and non–COVID‐19 individuals, respectively (OR = 0.93 for COVID patients, 95% CI = 0.87 to 0.99). Baseline characteristics associated with a higher risk of stroke in COVID‐19 patients were hypertension, diabetes mellitus, and previous cerebrovascular and coronary diseases. Clinically, these patients more frequently presented with confusion, decreased consciousness, and syncope and higher D‐dimer concentrations and leukocyte count at ED arrival. After adjustment for age and sex, the case group had higher hospitalization and intensive care unit (ICU) admission rates (but not mortality) than COVID‐19 controls without stroke (OR = 3.41, 95% CI = 1.27 to 9.16; and OR = 3.79, 95% CI = 1.69 to 8.50, respectively) and longer hospitalization and greater in‐hospital mortality than stroke controls without COVID‐19 (OR = 1.55, 95% CI = 1.24 to 1.94; and OR = 1.77, 95% CI = 1.37 to 2.30, respectively). Conclusions: The incidence of stroke in COVID‐19 patients presenting to EDs was lower than that in the non–COVID‐19 reference sample. COVID‐19 patients with stroke had greater need for hospitalization and ICU admission than those without stroke and longer hospitalization and greater in‐hospital mortality than non–COVID‐19 patients with stroke.